An introduction to twentieth-century poetry in English - Draper, Ronald P., 1928- (London : Macmillan, 1999)
This book is about: Modernism; An Alternative tradition; Private and Public; Poetry of two World Wars; ...
Keywords: English poetry; American poetry; Commonwealth poetry; English poetry -- 20th century -- History and criticism; American poetry -- 20th century -- History and criticism; Commonwealth poetry (English) -- History and criticism